Dominasi Peringkat RGEC Terhadap Laba Per Saham PT Bank Muamalat Indonesia Tbk - Husni Mubarok (Jurnal Ilmiah Ekonomi Islam, 2023)
The author takes a problem formulation which aims to determine the scientific statistical results of the RGEC Dominance ranking analysis of Earnings per Share at PT Bank Muamalat Indonesia Tbk 2008-2022. The research method uses quantitative numerical cases with a descriptive style design. This research uses secondary data techniques from the Annual Report of PT Bank Muamalat Indonesia Tbk 2008-2022 with variable analysis techniques using multiple regression and multiple correlation. The test results using the t test (partial test) of the Earnings indicator represented by Return on Assets (ROA) show that the most influence has a very strong positive value. H0 is accepted as a normally distributed residual on Earnings per Share, the test results using the F test (simultaneous test) prove that together -with the independent variable entity RGEC having a positive value is able to explain the very strong level of relationship between normally distributed residuals and Earnings per Share.